A review of gene- and cell-based therapies for familial hypercholesterolemia. (May 2019) - Hajighasemi, Saeideh; Mahdavi Gorabi, Armita; Bianconi, Vanessa; Pirro, Matteo; Banach, Maciej; Ahmadi Tafti, Hossein; Reiner, Željko; Sahebkar, Amirhossein
Graphical abstract: Abstract: Familial hypercholesterolemia (FH) is a genetic autosomal dominant disorder caused by an impaired receptor-mediated low-density lipoprotein (LDL) removal from the circulation, mainly due to disruptive autosomal co-dominant mutations in the LDL receptor ( LDLr ) gene, but also less frequently in the apolipoprotein B100 ( APOB ) and proprotein convertase subtilisin/kexin type 9 ( PCSK9 ) genes. A rare form of autosomal recessive FH has been also described due to LDLr adaptor protein 1 ( LDLRAP1 ) gene mutations. FH is characterized by very high levels of plasma LDL cholesterol associated with the high incidence of premature atherosclerotic cardiovascular disease (CVD). Despite heterozygous FH (HeFH) patients are still poorly recognized and treated, there is today a large availability of drugs ( i.e., statins, ezetimibe and PCSK9 inhibitors) allowing theoretically the normalization of plasma LDL cholesterol levels in this population. Homozygous FH patients (HoFH) have a more severe form of FH, characterized by low responsiveness to the conventional lipid-lowering treatment and often associated with unfavorable prognosis in the young age. Inspired by promising outcomes obtained by orthotopic liver transplantation (OLT), scientists are investigating the possibility of correcting the defective LDLr in these patients by using gene therapy approaches to achieve a novel therapeutic solution with high efficiency. In this article, we tried to review the in vitro, ex vivo, and in vivo attempts conducted to correct FH-causing LDLr gene mutations by using different methods of gene delivery, gene editing, and stem cell manipulation. We also discussed some clinical trials performed in this context.